Von Generation zu Generation Wie biografische Brüche in Familien weiterwirken - Abraham, Andrea (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
How do the daughters and sons of victims of coercive social measures suffer? Based on biographical inter-views, this anthology describes the consequences of repeated violence for the second generation and their efforts to prevent the third generation from also being affected by it. Until now, nothing was known about the damaging effects of such measures on offspring in Switzerland. In this book, the authors show that the second generation suffered from silence, proximity/distance problems and violence in their close social environment. Yet, these victims broke through the silence, created an autonomous life early on and are now privately and professionally committed to the welfare of other people. The authors of the anthology conducted research together over a period of three years and analysed the transgenerational transmission of trauma related to coercive measures using concepts and methods from social work, social pedagogy, social anthropology, the sociology of education and psychology. With contributions by Eveline Ammann Dula | Andrea Abraham | Kevin Bitsch | Nadine Gautschi | Regina Jenzer | Cynthia Steiner